Продуктивноста во контекст на зборообразувањето во англискиот јазик - Наумоска Саракинска, Билјана (Филолошки факултет, Скопје, 2018)
The productivity of word formation plays an important role in the expansion of the vocabulary of a given language, and, yet, the term productivity itself is perhaps one of the most controversial concepts in the studies connected to word formation. The issues raised are not so much in terms of whether certain word-formational are productive or not, but, rather, to what extent it may be claimed that word formation is productive in general. The term productivity is related to word formation in that it refers to the degree of use of a given grammatical structure in the formation of new words. There are a number of process that are employed in the formation of new words, some with a higher degree of productivity, others with a lower degree, and the English language makes use of almost all of them. In fact, the concept of productivity is not an either/or phenomenon, rather, it represents a gradation of morphological changes in a given group of related structures. The fact that certain tendencies are more productive than others cannot be disputed, even when other restrictions are taken into account. This, on the other hand, is closely related to lexicalization, and the ties that exist between productivity and lexicalization are relatively complex ones. Generally speaking, a given morphological process may be seen as productive according to the number of new forms that it has created. New forms of words appear on a regular basis in headlines and advertisements, for example, and people are undoubtedly aware of their appearance, as well as the new uses of the old forms of words. In this sense, the productive nature of word formation may be taken as a fact in any theory connected to it.
Keywords: word formation, productivity, restrictions, pragmatics, creativity, analogy, blocking, semantic consistency